Mirrors to Del Pezzo Surfaces and the Classification of -Polygons - Lutz, Wendelin (Symmetry, Integrability and Geometry: Methods and Applications, 2024)
We give a new geometric proof of the classification of -polygons, a theorem originally due to Kasprzyk, Nill, and Prince, using ideas from mirror symmetry. In particular, this gives a completely geometric proof that any two toric ℚ-Gorenstein degenerations of a smooth del Pezzo surface are connected via trees of rational curves in the moduli space of .